Analisis, Uji Coba dan Rekonstruksi Kegiatan Praktikum Melalui Lembar Kerja Peserta Didik Pencernaan Kimiawi: (Analysis, Testing and Reconstruction of Practical Activities Through Worksheets Chemical Digestion Students) - Siregar , Nurul Faizah; Supriatno , Bambang; Amprasto, Amprasto (BIODIK, 2024)
Practicum is an important component in biology learning and practicum helps students to gain hands-on experience. Practicum activities can be assisted by the presence of student worksheets. Student worksheets as a guide to the implementation process of practicum to improve student skills. This study aims to analyze and reconstruct student worksheets. The research method applied in this study uses a qualitative descriptive method. This study has research stages, namely ANCOR: Analysis, Trial, and Reconstruction. The student worksheet (LKPD) used is the 2013 Curriculum 8th grade science book Revised 2017. The results of the study show that LKPD on the concept of the chemical digestive system in the 2013 curriculum book revised 2017 has several components that must be reconstructed, besides that there are no changes in terms of content according to the curriculum. Therefore, it is necessary to improve LKPD on the concept of the chemical digestive system. The components that are improved in LKPD according to the knowledge construction adapted from Novak & Gowin (1984) include: Focus Question, Object Event, Theory/principle/concept, Record/transformation and Knowledge Claim. The components that are improved in LKPD include: activity objectives, theoretical basis, tools and materials, work steps, data recording and practical questions. This improvement is expected to provide an understanding that is in accordance with the revised 2013 curriculum, which can provide more meaningful practicums in addition to students being able to improve their minds on and hands on abilities in practical activities to face the era of the industrial revolution 4.0 Absrtak. Praktikum adalah komponen penting dalam pembelajaran biologi dan praktikum membantu siswa untuk memperoleh pengalaman langsung. Kegiatan praktikum dapat dibantu dengan adanya lembar kerja siswa. Lembar kerja peserta didik sebagai penuntun proses pelaksanaan praktikum untuk meningkatkan keterampilan peserta didik. Penelitian ini bertujuan untuk menganalisis dan merekonstruksi  lembar kerja peserta didik. Metode penelitian yang diterapkan dalam penelitian ini  menggunakan metode deskriptif kualitatif. Penelitian ini memiliki tahap penelitian yaitu ANCOR: Analisis, Uji Coba, dan Rekonstruksi. Lembar kerja peserta didik (LKPD) yang digunakan adalah buku kelas VIII IPA Kurikulum 2013 Revisi 2017. Hasil penelitian menunjukkan LKPD pada konsep sistem pencernaan kimiawi pada buku kurikulum 2013 revisi 2017 memiliki beberapa komponen yang harus direkonstruksi, selain itu tidak ada perubahan dalam hal konten sesuai dengan kurikulum. Maka dari itu, diperlukan perbaikan LKPD pada konsep sistem pencernaan kimiawi. Komponen yang diperbaiki pada LKPD sesuai dengan konstruksi pengetahuan yang diadaptasi dari Novak & Gowin (1984) antara lain: Focus Question, Object Even, Theory/principle/concept,Record/transformation dan Knowledge Claim.